Localized Surface Vibration and Acoustic Noise Emitted From Laboratory-Scale Transformer Cores Assembled From Grain-Oriented Electrical Steel - Anthony John Moses; Philip I. Anderson; Teeraphon Phophongviwat (My University, 2016)
s o n M a g n e tic s 5 2 (1 0) , -. 1 0.
Keywords: Magnetic Properties and Applications